Monosynaptic Retrograde Tracing From Prelimbic Neuron Subpopulations Projecting to Either Nucleus Accumbens Core or Rostromedial Tegmental Nucleus - Cruz, Adelis M.; Kim, Tabitha H.; Smith, Rachel J. (Frontiers in Neural Circuits, 2021)
The prelimbic (PL) region of medial prefrontal cortex (mPFC) has been implicated in both driving and suppressing motivated behaviors, including cocaine seeking in rats. These seemingly opposing functions may be mediated by different efferent targets of PL projections, such as the nucleus accumbens (NAc) core and rostromedial tegmental nucleus (RMTg), which have contrasting roles in reward-seeking behaviors. We sought to characterize the anatomical connectivity differences between PL neurons projecting to NAc core and RMTg. We used conventional retrograde tracers to reveal distinct subpopulations of PL neurons projecting to NAc core vs. RMTg in rats, with very little overlap. To examine potential differences in input specificity for these two PL subpopulations, we then used Cre-dependent rabies virus (EnvA-RV-EGFP) as a monosynaptic retrograde tracer and targeted specific PL neurons via injections of retrograde CAV2-Cre in either NAc core or RMTg. We observed a similar catalog of cortical, thalamic, and limbic afferents for both NAc- and RMTg-projecting populations, with the primary source of afferent information arising from neighboring prefrontal neurons in ipsilateral PL and infralimbic cortex (IL). However, when the two subpopulations were directly compared, we found that RMTg-projecting PL neurons received a greater proportion of input from ipsilateral PL and IL, whereas NAc-projecting PL neurons received a greater proportion of input from most other cortical areas, mediodorsal thalamic nucleus, and several other subcortical areas. NAc-projecting PL neurons also received a greater proportion of contralateral cortical input. Our findings reveal that PL subpopulations differ not only in their efferent target, but also in the input specificity from afferent structures. These differences in connectivity are likely to be critical to functional differences of PL subpopulations.